2010
DOI: 10.1021/ic101709q
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Bis(2,2,5,5-tetramethyl-2,5-disila-1-azacyclopent-1-yl)tin with CO2, OCS, and CS2 and Comparison to That of Bis[bis(trimethylsilyl)amido]tin

Abstract: The heterocumulenes carbon dioxide (CO(2)), carbonyl sulfide (OCS), and carbon disulfide (CS(2)) were treated with bis(2,2,5,5-tetramethyl-2,5-disila-1-azacyclopent-1-yl)tin {[(CH(2))Me(2)Si](2)N}(2)Sn, an analogue of the well-studied bis[bis(trimethylsilyl)amido]tin species [(Me(3)Si)(2)N](2)Sn, to yield an unexpectedly diverse product slate. Reaction of {[(CH(2))Me(2)Si](2)N}(2)Sn with CO(2) resulted in the formation of 2,2,5,5-tetramethyl-2,5-disila-1-oxacyclopentane, along with Sn(4)(μ(4)-O){μ(2)-O(2)CN[Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Unfortunately, the 13 C{ 1 H} NMR spectra of 4 and 5 did not exhibit resonances for the C S 2 carbon atoms, which were expected to be shifted to lower field compared to that of free CS 2 ( δ =192.6 ppm). Comparable findings were recently reported 22. Typically, values far above 200 ppm were reported,22,23 even though Limberg et al very recently observed a resonance at δ = 172.5 ppm for a dinuclear Cu‐CS 2 complex 24…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Unfortunately, the 13 C{ 1 H} NMR spectra of 4 and 5 did not exhibit resonances for the C S 2 carbon atoms, which were expected to be shifted to lower field compared to that of free CS 2 ( δ =192.6 ppm). Comparable findings were recently reported 22. Typically, values far above 200 ppm were reported,22,23 even though Limberg et al very recently observed a resonance at δ = 172.5 ppm for a dinuclear Cu‐CS 2 complex 24…”
Section: Resultssupporting
confidence: 53%
“…Comparable findings were recently reported 22. Typically, values far above 200 ppm were reported,22,23 even though Limberg et al very recently observed a resonance at δ = 172.5 ppm for a dinuclear Cu‐CS 2 complex 24…”
Section: Resultssupporting
confidence: 53%
“…35), such as an azoimide residue (99 [144]), amino group (100 [145]), acyl group (101 [146]), halogen (102 [147]), organophosphine (103 [148]), or isothiocyanate group (104 [149]. 103 [148] 104 [149] This is also true for the formation of polyhedral molecules containing only alkali metal ions, where these PHMSs are formed exclusively from organosilanolates (Fig. 36, 105 [150]), or with additional ligands such as alkoxy groups (Fig.…”
Section: Polyhedral Metallasiloxanes Based On Trisubstituted Organosimentioning
confidence: 99%
“…Most of these reports focus on the reactions of Me 3 SiCl with primary and secondary amines, e. g. using the TMS substituent as directing group in organic synthesis [19]. In contrast, we report here the use of Me 2 SiCl 2 and a primary amine as starting materials for the synthesis of diaminosilanes Me 2 Si(NHR) 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Hence, CO 2 is mainly used as a C1 source. One of the several methods known for the activation of CO 2 [2] is the insertion into a main group or transition metal nitrogen bond [3].…”
Section: Introductionmentioning
confidence: 99%